Assessment of the Possibility of Using Bacterial Strains and Bacteriophages for Epidemiological Studies in the Bioaerosol Environment - Radosław Wróbel; Monika Andrych-Zalewska; Jędrzej Matla; Justyna Molska; Gustaw Sierzputowski; Agnieszka Szulak; Radosław Włostowski; Adriana Włóka; Małgorzata Rutkowska-Gorczyca (Microbiology Research, 2024)
During the COVID-19 pandemic, microbiological controls neglected the spread of viruses through the air. Techniques to identify this threat required additional research to enable control measures to be introduced to protect against the spread of disease through this route. Due to the very high level of risk occurring during research on the COVID-19 and SARS-CoV-2 viruses, it seems necessary to use analogous microorganisms that will allow, through an experiment, to validate or challenge a method that stops the spread of infectious microorganisms, without unnecessary risk to research staff. The presented work was carried out to assess the possibility of using airborne microorganisms that are safe for humans for this type of research. The work presents the selection process of bacteria and viruses (bacteriophages) that have the greatest potential for use in experimental studies on airborne-droplet transmission indoors, especially in hospital facilities. In the study, it was assumed that determining the survival rates of groups of organisms would allow them to be used as a proxy for studying more dangerous bacteria and viruses. Survival studies of selected microorganisms were carried out, and the paper selected microorganisms with the highest survival rate in a given environment.